Raise of the functories to the Eilenberg-Moore monad generated by the functor C_pC_p - Pikhurko О. В.; Zarichnyi М. М. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The second iteration of contravariant functor of the space of continuous functions with topology of pointwise convergence is functorial part of a triple on the category of Tychonoff spaces. The problem of lifting of functors to the Eilenberg-Moore category of this triple is investigated.